2021
DOI: 10.1021/acs.jpclett.1c01518
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Spin-Controlled Enantioselective Catalytic Chiral Reactions

Abstract: Enantioselective catalytic chiral reactions are important to all aspects of life sciences. Here we present the first utilization of the chiral induced spin selectivity (CISS) effect to form, enantioselectively, sp 3 chiral centers in catalytic reactions, starting from achiral reagents. The enantiomeric symmetry is broken by affecting spin-controlled different reaction dynamics toward each of the enantiomers, using magnetic substrates. Two catalytic reactions are used for this purpose: a sulfide to sulfoxide ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
0
27
2
Order By: Relevance
“…This effect was observed in redox reactions that involve the transfer of spin-polarized electrons (8)(9)(10)(11). A magnetic catalyst has recently been used to make a product with asymmetric carbon when all the reactants are achiral (12).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was observed in redox reactions that involve the transfer of spin-polarized electrons (8)(9)(10)(11). A magnetic catalyst has recently been used to make a product with asymmetric carbon when all the reactants are achiral (12).…”
Section: Introductionmentioning
confidence: 99%
“…We can see a manifestation of this in the recent electrochemistry experiments with a magnetized electrode, where the electron spin direction enantioselectively affects the redox behavior of a chiral ferrocene derivative, Ugi’s amine, and camphorsulfonic acid ( 27 , 28 ). Similarly, it has been shown that chiral centers can be enantioselectively formed by a solid-state catalytic reaction on a magnetized hematite (Fe 2 O 3 ) surface due to enantioselective reaction kinetics by the CISS effect ( 29 ).…”
Section: Enantioselective Reduction Chemistrymentioning
confidence: 99%
“…Demonstration of the CISS effect using chiral molecules and its use in a variety of applications, including in enantioselection, , water splitting, , molecular spintronics, and biorecognition, is remarkable and is one of the most sought-after areas of research among academicians across the globe. The presence of structural asymmetry in the form of chirality in various biomolecules, such as DNA, proteins, and amino acids, leads to this observable effect when electrons pass through these molecules with a predefined quantization (of spin) axis.…”
Section: Introductionmentioning
confidence: 99%